Nanotechnology in cosmetic field - Кордіяка, Юлія Миронівна; Байцар, Роман Іванович (Technology audit and production reserves, 2014)
It was shown the general characteristic of nanomaterials which are used in cosmetic industry, it was studied their diversity and the principle of operation. There were raised issues about the accuracy of assessment methods of their safety for consumers' health and the environment. It was studied the international market of the producers of nanocosmetics and it was analyzed the major trends in domestic production. It was emphasized the importance of creating of a strong relevant regulatory and technical support in terms of social responsibility for the development of nanotechnology in the cosmetics industry. As a nanorevolution in the cosmetics industry cannot be ignored, moreover stopped, any inaccuracies in scientific risk assessment will cause a negative public attitude to nanotechnology, which can lead to slower development of new technologies.